2012
DOI: 10.1149/2.jes111637
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Reactivity of Na/Hard Carbon with Different Solvents and Electrolytes

Abstract: The reactivity of sodium inserted hard carbon with ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), EC:DEC, EC:DMC and NaPF 6 EC:DEC (/DMC) electrolytes was studied by Accelerating Rate Calorimetry (ARC), and the products after the ARC experiments were investigated by X-ray diffraction. The results show that sodium inserted hard carbon reacts with DMC to form sodium methyl carbonate, and that it reacts with EC and DEC to form sodium alkyl carbonates which apparently have a similar st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 19 publications
0
95
0
Order By: Relevance
“…Moreover, Na 2 O 2 is less stable than Li 2 O 2 , and this could be an advantage for Na-O 2 cells, with the feasibility to easily reach Na 2 O (a four-electron process) 97 . Safety wise there is no indication or scientific grounds to tell whether Na-ion batteries will be safer or not than Li-ion batteries, but preliminary accelerating rate calorimetry tests suggest that they will be at least as safe as Li-ion batteries 98,99 . The advancement of Na-ion technology is a certainty, but the type of market it will conquer remains unclear.…”
Section: Post-li Chemistriesmentioning
confidence: 99%
“…Moreover, Na 2 O 2 is less stable than Li 2 O 2 , and this could be an advantage for Na-O 2 cells, with the feasibility to easily reach Na 2 O (a four-electron process) 97 . Safety wise there is no indication or scientific grounds to tell whether Na-ion batteries will be safer or not than Li-ion batteries, but preliminary accelerating rate calorimetry tests suggest that they will be at least as safe as Li-ion batteries 98,99 . The advancement of Na-ion technology is a certainty, but the type of market it will conquer remains unclear.…”
Section: Post-li Chemistriesmentioning
confidence: 99%
“…5,6 For example, several positive electrode materials like We have also investigated the charge-discharge behavior of hard carbon (HC) negative electrodes in this ionic liquid at 363 K. 10,11 HC is mainly composed of two structural domains, i.e., randomly-arranged graphene domains and their interstitial sites (pores), and its charge-discharge behavior as a negative electrode material for sodium secondary batteries has been well investigated in organic solvent electrolytes. [12][13][14][15][16][17][18][19][20] However, there have been few studies on the correlation of HC structure and its electrochemical behavior in ionic liquid electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the SEI on HC in NIBs containsm any inorganic speciest hat are nonhomogeneous and porousi nn ature. Xia et al [10][11][12] studied the thermal response of Na x -HC in the presenceo fv arious salts, such as NaPF 6 and sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), and solvent mixtures by using accelerated-rate calorimetry (ARC). In this study,aNaPF 6 -based electrolyte was more reactive than NaTFSIt owards sodiated HC because of the high thermals tabilityo fN aPF 6 ,w hich resultsi nthe absence of NaF in the SEI layer.M oreover,i nt he presence of NaPF 6 ,D MC and DEC are more reactive than EC if in contact with Na x -HC because of the preferentials olvationo fN a + + by EC, which leaves DMC and DECint he outer sphere.…”
mentioning
confidence: 99%